Right-way fire in Australia's spinifex deserts: An approach for measuring management success when fire activity varies substantially through space and time. (1st April 2023) - Ruscalleda-Alvarez, Jaume; Cliff, Hannah; Catt, Gareth; Holmes, Jarrad; Burrows, Neil; Paltridge, Rachel; Russell-Smith, Jeremy; Schubert, Andrew; See, Peter; Legge, Sarah
Abstract: Indigenous Australians used fire in spinifex deserts for millennia. These practices mostly ceased following European colonisation, but many contemporary Indigenous groups seek to restore 'right-way fire' practices, to meet inter-related social, economic, cultural and biodiversity objectives. However, measuring and reporting on the fire pattern outcomes of management is challenging, because the spatio-temporal patterns of right-way fire are not clearly defined, and because spatio-temporal variability in rainfall makes fire occurrence highly variable in these desert environments. We present an approach for measuring and reporting on fire management outcomes to account for spatio-temporal rainfall variability. The purpose is to support Indigenous groups to assess performance against their management targets, and lay the groundwork for developing an accredited method for valuing combined social, cultural and biodiversity outcomes. We reviewed fire management plans of desert Indigenous groups to identify spatial fire pattern indicators for right-way fire in spinifex deserts. We integrated annual rainfall surfaces with time-since fire mapping (using Landsat imagery) to create a new spatial dataset of accumulated rainfall-since-last-fire, that better represents post-fire vegetation recovery as categorised by local Indigenous people. The fire pattern indicators were merged into a single score using an environmental accounting approach. To strengthen interpretation, we developed an approach for identifying a control area with matching vegetation and fire history, up to the point of management. We applied these methods to a 125, 000 ha case study area: Durba Hills, managed by the Martu people of Western Australia. Using a 20-year time series, we show that since right-way fire management at Durba Hills was re-introduced (2009), the fire pattern indicators have improved compared to those in the matched control area, and the composite result is closer to the fine-scaled mosaic of right-way fire pattern targets. Our approach could be used by Indigenous groups to track performance, and inform annual fire management planning. As the indicators are standardised for rainfall variation, results from multiple sites can be aggregated to track changes in performance at larger scales. Finally, our approach could be adapted for other fire-prone areas, both in Australia and internationally with high spatio-temporal rainfall variability, to improve management planning and evaluation. Highlights: Measuring changes in fire patterns in areas with variable rainfall is challenging. Integrating rainfall with fire history data improves estimates of spatial patterns. Fire pattern indicators were combined using an environmental accounting framework. We tested the approach in a desert area managed by Indigenous Australians. Fire management over 10 years is pushing fire towards a pre-colonisation pattern.